An Inquiry Relative to Preparation for a General World Administrative Radio Conference of the International Telecommunication Union to Consider Revision of the International Radio Regulations Report and Order before the Federal Communications Commission, Washington, D.C. Docket No. 20271. - Federal Communications Commission, Washington, DC.; Federal Communications Commission, Washington, DC. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This "Report and Order" from the Federal Communications Commission (FCC) represents the examination of thousands of comments and an expert determination of the future needs of the nongovernmental users of the radio spectrum in the United States. The proposals it contains will be part of the United States' proposals at the 1979 World Administrative Radio Conference of the International Telecommunication Union. It includes a background of the report; terminology and rules for the use of frequencies; table of frequency allocations; technical proposals; regulatory proposals; and administrative, operational, and miscellaneous proposals, along with associated appendixes. It is preceded by a statement by FCC chairman Charles D. Ferris and by a joint statement by Commissioners Abbott Washburn and James H. Quello. (TJ)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication (Thought Transfer); Federal Government; Federal Regulation; Radio; Federal Communications Commission; Legal/Legislative/Regulatory Materials